Indium(III) Chloride Promoted Highly Efficient Tandem Rearrangement–α-Addition Strategy towards the Synthesis of α-Hydroxyamides - Lingaswamy, Kadari; Mohan, Dumpala; Krishna, Palakodety Radha; Prapurna, Y. Lakshmi (Synlett, 2016)
A new tandem process is reported that provides access to α-hydroxyamides from epoxides for the first time. Herein, we explore InCl3-mediated tandem rearrangement of epoxides to aldehydes and α-addition of TosMIC to in situ derived aldehydes. An unprecedented C–C bond-forming reaction is disclosed that features mild conditions, high yields, and shorter reaction times.
Keywords: C–C bond formation; indium(III) chloride; epoxides; TosMIC; tandem rearrangement; α-addition